2016
DOI: 10.1177/1049909115615568
|View full text |Cite
|
Sign up to set email alerts
|

Building Community Capacity in Bereavement Support

Abstract: Bereaved family caregivers' experiential knowledge can be harnessed to progress the development of bereavement care strategies for the good of the community. These responses could be incorporated into information brochures, posters, and other community education avenues in order to upskill palliative care bereavement volunteers and the wider community so that bereaved family caregivers are best supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
3
31
0
1
Order By: Relevance
“…They also appreciated accessing the information in their own time. This is consistent with others who reported that most bereaved individuals benefit from receiving appropriate written information or brochures . This type of written support has been shown to provide a sense of certainty and security for families .…”
Section: Discussionsupporting
confidence: 88%
“…They also appreciated accessing the information in their own time. This is consistent with others who reported that most bereaved individuals benefit from receiving appropriate written information or brochures . This type of written support has been shown to provide a sense of certainty and security for families .…”
Section: Discussionsupporting
confidence: 88%
“…However, it is clear that a considerable proportion of bereaved people experience isolation/lack of support and poor health, which they connect to the experience of being bereaved. 21 23 …”
Section: Discussionmentioning
confidence: 99%
“…However, it is clear that a considerable proportion of bereaved people experience isolation/lack of support and poor health, which they connect to the experience of being bereaved. [21][22][23] Sources of support and their perceived helpfulness Aoun and colleagues 1 concluded that, apart from everyone needing informal support from their social networks, more than two-fifths of people required some other form of bereavement support (35% community and 6% professional). More centrally, they noted that those most at risk of complications in grieving were accessing formal professional services and those at moderate risk were accessing community-based services.…”
Section: Impact Of Bereavementmentioning
confidence: 99%
“…In fact, we have previously reported that the majority of the bereaved in each of the 3 risk groups accessed support predominantly from family (95%) and friends (88%), followed by funeral directors (79%) and general practitioners (56%) [ 18 ], emphasized also in Fig 2 . Therefore, palliative care services might do better investing their efforts principally in (a) assessing and supporting family caregivers during the pre-bereavement period and (b) developing community capacity and referral pathways for bereavement care [ 18 , 25 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%